How Juvenile Criminal Justice System in Indonesia Works? A Book Review 'Peradilan Pidana Anak di Indonesia', Marlina, PT Refika Aditama, Jakarta, 2009, 232 Pages, ISBN 9798-602-8650-06-9 - Chandra, Safari Dwi (Universitas Negeri Semarang, 2021)
Human needs to live in an orderly, harmonious, harmonious, and peaceful manner are still maintained in accordance with applicable law. To provide security to every citizen, law enforcement officials need to take action by carrying out legal proceedings against criminal offenders. The implementation of legal proceedings against criminal offenders is in a system consisting of related subsystems called the criminal justice system or in the English Criminal Justice System. This book is divided into four chapters, an introduction; children in conflict with the law; juvenile criminal justice; the development of the concept of diversion, and restorative justice. Actually, this book only discusses one important point, namely regarding chapter 4, the development of the concept of diversion and restorative justice. However, the author makes the translation first by writing chapters 1 through chapter three.